Effects of Audit Quality and Audit Committee Characteristics on Earnings Management During the Global Financial Crisis – Evidence from Australia - Abu T. Mollik; Monir Mir; Ron McIver; Md. Khokan Bepari (Australasian Accounting, Business and Finance Journal, 2020)
Purpose: We examine the earnings management behaviour of Australian firms during the Global Financial Crisis (GFC) and the effectiveness of audit quality and audit committee characteristics in mitigating such behaviour. Design/methodology/approach: The sample consists of 503 firm-year -observations spanning from 2006 to 2009. The years 2008 and 2009 are considered as the global financial crisis period. Discretionary accruals have been used as the proxy for earnings management. To test the hypothesis, we apply multivariate fixed effect regression to test the hypothesis. As the robustness test, we use propensity matching score, to find out comparable clients audited by Big-4 and Non-Big-4 audit firms to control observations to mitigate the effect of selection bias. Findings: We find that the sampled firms engage in a significantly higher level of earnings management during the GFC compared to the pre-crisis period (PCP). We find that audit quality, in terms of being audited by Big4 auditors, constrains earnings management during the PCP, but not during the GFC. Audit committee independence has a significant mitigating effect on firms' earnings management, while audit committee members' accounting and finance expertise do not constrain earnings management. Research limitations/implications: Future research can include a larger sample and examine the effects of other corporate governance variables on earnings management during periods of macroscopic shocks. Practical implications: Our findings support the importance of having independent directors in the audit committee. Moreover, the fact that Big4 auditors do not constrain earnings management during the GFC although constraining it during the PCP implies that regulators and policy makers should concentrate more on the audit committee for effective mitigation of earnings management during periods of macroeconomic shock. Originality/value: A key policy implication of the findings is that regulators and standard setters may need to shift their focus from the quality of a firm's auditor to encouraging well-functioning audit committees. The specific action to promote audit committee effectiveness includes mandating independence.
Keywords: Earnings management; global financial crisis; audit quality; audit committee